Dispensing of drugs with and without a prescription from private pharmacies in Dar es Salaam (Tanzania Medical Journal, 2007)
There is little literature available on dispensing patterns and unsupervised sale of medicines from pharmacies in Tanzania. The present study assessed the patterns of drug acquisition from pharmacies by customers: whether by prescription, recommended by pharmacist, or requested by a customer without a prescription. The counseling accompanying the dispensing of these drugs was also assessed.Two three- hour observational visits were made to each of the twenty pharmacies to collect data. A total of 378 customers who visited the pharmacies were observed. Out of these, 64.29% requested a particular drug, 17.46% came in with a health problem seeking for advice, while 18.25% presented a prescription from a doctor. Of the total drugs demanded 37.08 % were “prescription only drugs”. Counseling of customers on drugs purchased was poor and drugs dispensed were not properly labeled. Among patients presenting with common ailments, patients with cough were the most encountered (25.76%). The pharmacy staff did not offer appropriate advice when faced with people having health related problems. The study highlights the need to reinforce laws governing sales and dispensing of drugs. There is need to educate the general public about self-medication so that people may practice responsible self-medication and stop self medicating using “prescription only” drugs. Keywords: Self-medication, prescription only drugs, over the counter drugs, dispensing Tanzania Medical Journal Vol. 19 (1) 2004